Anti‐metabotropic glutamate receptor 5 encephalitis: Five case reports and literature review - Sixian Chen; Haitao Ren; Fuhong Lin; Siyuan Fan; Yuze Cao; Weili Zhao; Hongzhi Guan; the Encephalitis Collaborative Group (Brain and Behavior, 2023)
Abstract Objective To describe the clinical and radiological characteristics of anti‐metabotropic glutamate receptor 5 (mGluR5) encephalitis. Methods We reviewed the clinical data of five patients with anti‐mGluR5 encephalitis, and performed a literature review. Results The five cases included a 52‐year‐old man who developed a biphasic course of anti‐mGluR5 encephalitis after herpes simplex encephalitis, a 22‐year‐old woman who showed bilateral basal ganglia lesions on brain magnetic resonance imaging (MRI), and a 36‐year‐old man with mixed aphasia and generalized tonic‐clonic seizures, a 51‐year‐old man presented with personality changes, hallucinations, delusions, sleeping disorders and a 58‐year‐old man with short‐term memory deficits and absence seizures.. There are 16 reported cases of anti‐mGluR5 encephalitis worldwide. Of all 21 patients, with a median onset age of 35 years old, the main neurological symptoms were cognitive impairment (85.7%, 18/21), psychiatric or behavior problems (76.2%, 16/21), seizures (57.1%, 12/21), sleeping disorders (52.4%, 11/21), different degrees of decreased consciousness (42.9%, 9/21), and movement disorders (23.8%, 5/21). Brain MRI was normal in 11 of 21 patients. Lesions of the limbic lobes were presented in 5 patients, while involvement of other extralimbic regions was also reported. Seven of 21 (33.3%) cases were combined with tumors. Elevated white blood cell counts or specific oligoclonal IgG bands in the cerebrospinal fluid were found in 18 of 21 patients, with marked improvements observed after immunotherapy. Discussion Patients with anti‐mGluR5 encephalitis typically present with diffuse, rather than purely limbic, encephalitis. Anti‐mGluR5 encephalitis can be triggered by herpes simplex encephalitis. The risk of a combined tumor may be reduced in anti‐mGluR5 encephalitis patients.